Разработка стилизованного сервиза на основе творчества К. С. Малевича - Зверева К. М. Карина Махировна; Радченко В. Ю. Валерия Юрьевна; Давыдова Е. М. Евгения Михайловна; Ризен Ю. С. Юлия Сергеевна (2015, 2015)
Заглавие с экрана